Particle size influence on the chemical composition from waste Eucalyptus in the processing for industrial production of cellulose pulp - Neto, Flávia Sanchez Penalva P. [UNESP]; De Lucca, Edwil Aparecida [UNESP]; Masarin, Fernando [UNESP] (My University, 2016)
Among the biological materials, wood is a chemist and biochemist collection formed and organization still is of secrets and unknowns, despite the great technological advances in recent decades. Today the chemistry of wood takes new directions and new challenges with the technological improvement of the analysis and the emergence of wood modified by genetic modification, mutation and genetic improvement, therefore, new skills are required with new sources of information. Thus the present assessed chemical characterization a residue derived from Eucalyptus processing for the industrial production of cellulose pulp. Ten grams of sample were subjected to a milling process. The following particle sizes were studied (10, 14, 20, 30, 40 and 50 mesh). It was determined the moisture content, ash content and lignin were determined by the sum of Klason lignin insoluble and soluble lignin. The filtrate produced by the method insoluble Klason lignin was analyzed by spectroscopy. The holocelulose content, pulp and polyoses were determined through analysis by líquidade high performance liquid chromatography. The results showed that particle size influences the chemical properties of lignocellulosic material, and the smaller the particle size the greater was the amount of extractives and ash, which resulted in lower amounts of cellulose and hemicellulose. Lignin showed no significant changes.